Infestation, survey and identification of fruitflies and their natural enemies in coffee - PORTILLA, MARIBEL; GONZÁLEZ-G., GLORIA; NUÑEZ-BUENO, LIGIA (Revista Colombiana de Entomología, 1994)
The study presented here about infestation, recognition, fluctuation, and identification of fruits flies and its natural enemies in coffee berries was developed in Tangua and Yacuanquer (Nariño Colombia), at 1,680 and 1,750 masl, with a mean relative humidity of 77,79%, and a mean temperature of 23°C. The specimens were identified at the ICA ’s Sanidad Vegetal Laboratory and at the University of Nariño Insect Collection in Pasto. The fruits file species reported attacking coffee berry were: Ceratitis capitata, Anastrepha fraterculus, and Neosilba glaberrima. Three species of fruit fly parasites were identified: Doryctobracon crawfordi, Opius anastrephae, and Microcrasis n.sp. The total parasitism percentage was 3,48%. The infestation by the fruit flies was 17,69%, the number of larvae/ kg of dry berries was 159,62 and the average number of larvae/berry was 1,4. The highest percentage of infestation occurred at the end of the harvest time and during the dry season.